Through Trial & Error to Collusion - The Discrete Case - Steffen Huck; Hans-Theo Normann; Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
In this note we study a very simple trial & error learning process in the context of a Cournot oligopoly. Without any knowledge of the payoff functions players increase, respectively decrease, their quantity by one unit as long as this leads to higher profits. We show that despite the absence of any coordination or punishing device this process converges to a collusive outcome.
Keywords: C72; L13; 330; learning; Cournot oligopoly